PENGARUH EDUKASI KESEHATAN GIGI TERHADAP PENGETAHUAN DAN KETERAMPILAN PENCEGAHAN KARIES PADA ANAK PRASEKOLAH - Elisabeth Dewi Puspitaningrum; Fathia Michella Taurisandy Putri; Bernike Anastasia Tarigan (Forind Press, 2026)
Dental and oral health problems, particularly dental caries, remain prevalent among preschool children in Indonesia. This study aims to analyze the effect of dental and oral health education on improving knowledge and skills in preventing dental caries. A quantitative approach with a pre-experimental one group pre-test and post-test design was employed. The subjects consisted of 23 children aged 3–5 years at Aulia Children Learning Center Pamulang. The intervention was conducted through interactive counseling and tooth brushing practice. Data were collected using simple questionnaires and observation sheets and analyzed using descriptive and inferential statistics with the Wilcoxon Signed-Rank test. The results showed an increase in the mean knowledge score from 56.52 to 86.96 and skills from 52.17 to 82.61. Statistical analysis indicated a significant difference before and after the intervention (p < 0.05). In conclusion, dental and oral health education is effective in improving knowledge and skills in preventing dental caries among preschool children. Practice-based education is recommended as an early promotive and preventive strategy.